DEVELOPING MANAGERS’ INTERCULTURAL COMPETENCE IN SMALL MANUFACTURING ENTERPRISES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Diverse and multicultural environment requires that managers of manufacturing enterprises should be able to work with representatives of different cultures. Seeking to maintain long-term commercial relationships, employees should strive for high level of intercultural competence through constant development. Object of the study – development of intercultural competence of managers. Aim of the study – to assess the development of intercultural competence of managers of small manufacturing enterprises. The qualitative research revealed that managers of small manufacturing companies develop intercultural competence informally, by learning from their own experiences, interacting and communicating in different intercultural situations with foreign customers, buyers, and suppliers. It was identified that the primary obstacle to intercultural communication is the inadequate foreign language proficiency of managers. Small manufacturing enterprises do not contribute to the development of managers' intercultural competence. It is noteworthy that the managers develop their intercultural competence in work setting, by sharing intercultural experiences, especially when they face with challenges or when work in unfamiliar cultural environments or unexpected situations. It can be stated that the Story Circles is an appropriate method for developing the intercultural competence of managers in small manufacturing and export companies with limited financial and human resources.